Financial time series forecasting (Stock prediction) - Chen, Hai Hui (2016)
Accurate prediction of stock price trend greatly helps stock investor to react correctly in the stock market. The unsteadiness of the stock market has caused serious profit loss to many people. Stock markets are easily affected by many factors. It includes financial, political and unknown company development. In order for one to make profit from the stock market, it needs adequate forecast to plan the future. Hence, effective, stable and accurate methods which able to build a model to have the ability to predict the stock market trend are needed.